Pengaruh Online Customer Rating dan Online Customer Review terhadap Keputusan Pembelian Produk The Originote pada Marketplace Shopee - Fahruddin, Muhammad Irfan; Aminah, Siti (Universitas Batanghari Jambi, 2025)
This research aims to investigate the influence of online customer ratings and online customer reviews on purchasing decisions for Originate products on the Shopee Marketplace. The method used is quantitative with a PLS (partial least square) analysis approach. The sampling technique applied was non-probability sampling with special criteria established in this research, so the number of samples used was 140 respondents. The results of this research indicate that online customer ratings and online customer reviews influence the decision to purchase the Originote product on the Shopee marketplace